Anxiolytic effect of minocycline in posttraumatic stress disorder model of Syrian hamsters - Panini Shrikant Patankar; Shirish Joshi; Abhishek Mane; P S Manjesh; Dhananjay Kokate (Tzu Chi Medical Journal)
Objective: The objective was to study the anxiolytic effect of minocycline in resident–intruder social conflict in submissive hamsters post resident intrusion model using open field test (OFT) and elevated plus maze (EPM) and serum cortisol levels. Materials and Methods: Fifty-two singly housed male Syrian hamsters were used, post standardization of an animal model. Resident intrusion was done (5 min), in which smaller hamsters were placed in the cage of larger hamster, and the behavior of smaller hamster was noted. Eight submissive hamsters per group (disease control, lorazepam group as a positive control, and the test drug was minocycline) were used, and the drug was administered immediately post resident intrusion, intraperitoneally. Behavioral tests, namely OFT and EPM, were done followed by retro-orbital blood collection for serum cortisol estimation. The level of significance was set at P < 0.05. Results: The minocycline group showed a statistically significant decrease in serum cortisol levels compared to the disease control group. Among all the variables pertaining to both the behavioral tests, namely EPM and OFT, the results indicated an anxiolytic effect, which was statistically significant compared to the disease control group. Conclusion: As per the biochemical test using serum cortisol levels and behavioral tests in the form of EPM and OFT, the study concluded that the anxiolytic effect of minocycline is at least comparable to the positive control, lorazepam.